Implementation of a Chatbot System using AI and NLP (International Journal of Innovative Research in Computer Science & Technology, 2018)
For using software applications, user  interfaces that can be used includes command line,  graphical user interface (GUI), menu driven,  form-based, natural language, etc. The mainstream user  interfaces include GUI and web-based, but occasionally  the need for an alternative user interface arises. A  chatbot based conversational user interface fits into this  space. The chatbot is a class of bots that have existed in  the chat platforms. The user can interact with them via  graphical interfaces or widgets, and the trend is in this  direction. They generally provide a stateful service i.e.  the application saves data of each session. On a college’s  website, one often doesn’t know where to search for  some kind of information. It becomes difficult to extract  information for a person who is not a student or  employee there. The solution to these comes up with a  college inquiry chat bot, a fast, standard and  informative widget to enhance college website’s user  experience and provide effective information to the user. Chat bots are an intelligent system being developed  using artificial intelligence (AI) and natural language  processing (NLP) algorithms. It has an effective user  interface and answers the queries related to  examination cell, admission, academics, users’  attendance and grade point average, placement cell and  other miscellaneous activities.
Keywords: Artificial intelligence; chat bot; knowledge base; lemmatization; natural language processing; semantic sentence similarity; wordnet